1983
DOI: 10.1063/1.332436
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of hydrogenated amorphous silicon films with transparent conductive films

Abstract: A real time ellipsometry study of the growth of amorphous silicon on transparent conducting oxides Effect of the surface condition on the conductance of hydrogenated amorphous silicon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…To explain the formation of the metallic In precipitates, we considered the chemical reduction of In 2 O 3 . It has been reported that indium‐oxide‐based TCO films are relatively readily reduced by exposure to a strongly reducing environment such as hydrogen plasma and that metal precipitates can be formed as a result . As we applied a negative bias to the cells in our PID tests, the cells corresponded to the cathode in oxidation‐reduction reactions.…”
Section: Discussionmentioning
confidence: 99%
“…To explain the formation of the metallic In precipitates, we considered the chemical reduction of In 2 O 3 . It has been reported that indium‐oxide‐based TCO films are relatively readily reduced by exposure to a strongly reducing environment such as hydrogen plasma and that metal precipitates can be formed as a result . As we applied a negative bias to the cells in our PID tests, the cells corresponded to the cathode in oxidation‐reduction reactions.…”
Section: Discussionmentioning
confidence: 99%
“…IOH and ITO layers were covered by a thin sputtered aluminum-doped ZnO layer of thickness t ¼ 20 nm which serves as a protective barrier layer against the hydrogen-rich plasma during the subsequent cell deposition. [25][26][27] This ZnO layer influences neither the optical nor the electrical measurements on the IOH and ITO films observably, as its much lower carrier density renders it very transparent and much more resistive than IOH and ITO. As ZnO also has a similar refractive index as IOH and ITO, no signficant reflection occurs at the IOH-ZnO and ITO-ZnO interface.…”
Section: à6mentioning
confidence: 99%
“…In case of W-textured FTO samples, thin ZnO:Al was deposited by sputtering on FTO before cell fabrication in order to avoid SnO 2 reduction by atomic H [27]. illumination.…”
Section: Mc-si:h Cell Fabricationmentioning
confidence: 99%